Programmable Unlocking Nano‐Matryoshka‐CRISPR Precisely Reverses Immunosuppression to Unleash Cascade Amplified Adaptive Immune Response. Issue 13 (14th May 2021) - Yang, Jin; Li, Zhike; Shen, Meiling; Wang, Yan; Wang, Li; Li, Jiamiao; Yang, Wen; Li, Jie; Li, Haijun; Wang, Xinxin; Wu, Qinjie; Gong, Changyang
Abstract: Immune checkpoint blockade (ICB) is an attractive option in cancer therapy, but its efficacy is still less than expected due to the transient and incomplete blocking and the low responsiveness. Herein, an unprecedented programmable unlocking nano‐matryoshka‐CRISPR system (PUN) targeting programmed cell death ligand 1 (PD‐L1) and protein tyrosine phosphatase N2 (PTPN2) is fabricated for permanent and complete and highly responsive immunotherapy. While PUN is inert at normal physiological conditions, enzyme‐abundant tumor microenvironment and preternatural intracellular oxidative stress sequentially trigger programmable unlocking of PUN to realize a nano‐matryoshka‐like release of CRISPR/Cas9. The successful nucleus localization of CRISPR/Cas9 ensures the highly efficient disruption of PD‐L1 and PTPN2 to unleash cascade amplified adaptive immune response via revoking the immune checkpoint effect. PD‐L1 downregulation in tumor cells not only disrupts PD‐1/PD‐L1 interaction to attenuate the immunosurveillance evasion but also spurs potent immune T cell responses to enhance adaptive immunity. Synchronously, inhibition of JAK/STAT pathway is relieved by deleting PTPN2, which promotes tumor susceptibility to CD8 + T cells depending on IFN‐ γ, thus further amplifying adaptive immune responses. Combining these advances together, PUN exhibits optimal antitumor efficiency and long‐term immune memory with negligible toxicity, which provides a promising alternative to current ICB therapy. Abstract : Programmable unlocking nano‐matryoshka‐CRISPR (PUN) possesses multistage sensitive properties and exhibits excellent performances, including prolonged blood circulation, precise tumor recognition, deep tumor penetration, robust lysosomal escape, and effective transfection. With the precise control of CRISPR/Cas9 activation, PUN realizes complete and thorough intracellular disruption of PD‐L1 and PTPN2, thus eliciting cascade amplified adaptive immune response to boost antitumor immune effects.